Impact of incomplete plan to treatment results of concurrent weekly cisplatin and radiotherapy in locally advanced cervical cancer - Ekkasit Tharavichitkul (2018)
To evaluate the efficacy of incomplete treatment protocols of cisplatin in concurrent chemoradiation for locally advanced cervical carcinoma. This retrospective study was performed in 165 consecutively treated patients with locally advanced cervical cancer who received a weekly cisplatin regimen. The number of weekly cisplatin cycles of each patient was recorded and used to discriminate between patients. Local control, disease free survival, distant metastasis-free survival, and toxicities were calculated using the software package SPSS version 15.0. Ninety-two patients (55%) completed the planned protocol of six cycles of weekly cisplatin. With the median follow-up time of 38.2 months, the 3-year local control rate differed significantly in the two patient groups (95.4% of 6 cycles versus 84.8% of < 6 cycles; p = 0.028). No statistical significance was observed for disease-free survival (74.6% versus 74.5%; p = 0.22) and distant metastasis-free survival (76.5% vs. 75.7%; p = 0.88). In conclusion, the plan completion of concurrent cisplatin with radiotherapy was responsible for better local control. However, differences in disease-free survival and distant metastasis-free survival were not statistical significant.